Novel assembly of BiVO4@N-Biochar nanocomposite for efficient detoxification of triclosan. (July 2022) - Wei, Xueyu; Xu, Xiaoping; Yang, Xiaofan; Liu, Zhigang; Naraginti, Saraschandra; Sen, Lin; Weidi, Song; Buwei, Li
Abstract: The wide spread of antibacterial and antifungal agents demands in growing multifunctional materials to completely eliminate these organic contaminants in water. BiVO4 (Bismuth vanadate) is a superior catalyst under visible light but suffers with high photoelectron-hole pair recombination rate and poor adsorption capacity which limits its efficiency. Addition of N-doped Biochar (N-Biochar) to BiVO4 with large specific surface area and high conductivity are anticipated to overcome the problem and promote the catalytic performance. Thus, the present study developed a simple hydrothermal method to prepare BiVO4 @N-Biochar catalyst for efficient detoxification of Triclosan (TCS). The morphological analysis results suggested that BiVO4 particles were evenly distributed on carbon surface amongst the N-Biochar matrix. Within 60 min of visible light irradiation, nearly 94.6% TCS degradation efficiency was attained by BiVO4 @N-Biochar (k = 0.02154 min −1 ) while only 56.7% was attained with pure BiVO4 (k = 0.00637 min −1 ). In addition, LC-MS/MS technique was utilized to determine the TCS degradation products generation in the photodegradation process and pathway was proposed. Furthermore, the E. coli ( Escherichia coli ) colony forming unit assay was used to determine the biotoxicity of the degradation products in which 72.3 ± 2.6% of detoxification efficiency was achieved and suggested a substantial reduction in biotoxicity during the photodegradation. Graphical abstract: Image 1 Highlights: Novel BiVO4 @N-biochar assembly was prepared by simple hydrothermal method. Stability of BiVO4 was effectively increased upon addition of N-biochar. N-Biochar and BiVO4 promoted the separation of photogenerated carriers. About 72.3 ± 2.6% of detoxification efficiency was achieved in 60 min. The main ROS for the TCS degradation were in the order of .OH > O2 – > h +